Conventional and emerging strategies for the fabrication and functionalization of PDMS-based microfluidic devices. Issue 16 (21st July 2021) - Shakeri, Amid; Khan, Shadman; Didar, Tohid F.
Abstract : The review paper presents a variety of methods for fabrication of PDMS-based microfluidic channels. Moreover, different strategies for tailoring the surface properties of PDMS microchannels and immobilization of biomolecules are discussed. Abstract : Microfluidics is an emerging and multidisciplinary field that is of great interest to manufacturers in medicine, biotechnology, and chemistry, as it provides unique tools for the development of point-of-care diagnostics, organs-on-chip systems, and biosensors. Polymeric microfluidics, unlike glass and silicon, offer several advantages such as low-cost mass manufacturing and a wide range of beneficial material properties, which make them the material of choice for commercial applications and high-throughput systems. Among polymers used for the fabrication of microfluidic devices, polydimethylsiloxane (PDMS) still remains the most widely used material in academia due to its advantageous properties, such as excellent transparency and biocompatibility. However, commercialization of PDMS has been a challenge mostly due to the high cost of the current fabrication strategies. Moreover, specific surface modification and functionalization steps are required to tailor the surface chemistry of PDMS channels ( e.g. biomolecule immobilization, surface hydrophobicity and antifouling properties) with respect to the desired application. While significant research has been reported in the field of PDMS microfluidics, functionalization of PDMS surfaces remains a critical step in the fabrication process that is difficult to navigate. This review first offers a thorough illustration of existing fabrication methods for PDMS-based microfluidic devices, providing several recent advancements in this field with the aim of reducing the cost and time for mass production of these devices. Next, various conventional and emerging approaches for engineering the surface chemistry of PDMS are discussed in detail. We provide a wide range of functionalization techniques rendering PDMS microchannels highly biocompatible for physical or covalent immobilization of various biological entities while preventing non-specific interactions.